2020
DOI: 10.3389/fmed.2020.00234
|View full text |Cite
|
Sign up to set email alerts
|

Lytic Activity of Polyvalent Staphylococcal Bacteriophage PhiSA012 and Its Endolysin Lys-PhiSA012 Against Antibiotic-Resistant Staphylococcal Clinical Isolates From Canine Skin Infection Sites

Abstract: Nakamura et al. Bacteriophage and Endolysin Against Antibiotic-Resistant-Staphylococci results demonstrated that ARB issues underlying in small animal hospital and proposed substitutes for antibiotics. Lys-phiSA012 has broader lytic activity than phiSA012 against staphylococcal isolates; therefore, Lys-phiSA012 is a more potential candidate therapeutic agent for several staphylococcal infections including that of canine skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…To address the issues associated with the current S. pseudintermedius phages, two recent independent studies have explored the potential use of lytic Staphylococcus aureus phages with broad host ranges against S. pseudintermedius isolates [ 128 , 130 ]. Results from both studies showed that while the S. aureus phages tested (ɸSA039 and phiSA012) did possess a broad host range, able to infect S. aureus, S. pseudintermedius, S. schleiferi and CoNS, they both showed only weak to moderate infectivity towards S. pseudintermedius [ 128 , 130 ]. Therefore, further work is required to determine if the lytic activity of lytic S. aureus phages is sufficient enough to exploit their use in treating S. pseudintermedius canine infections.…”
Section: Current and Future Treatment Options For Staphymentioning
confidence: 99%
See 1 more Smart Citation
“…To address the issues associated with the current S. pseudintermedius phages, two recent independent studies have explored the potential use of lytic Staphylococcus aureus phages with broad host ranges against S. pseudintermedius isolates [ 128 , 130 ]. Results from both studies showed that while the S. aureus phages tested (ɸSA039 and phiSA012) did possess a broad host range, able to infect S. aureus, S. pseudintermedius, S. schleiferi and CoNS, they both showed only weak to moderate infectivity towards S. pseudintermedius [ 128 , 130 ]. Therefore, further work is required to determine if the lytic activity of lytic S. aureus phages is sufficient enough to exploit their use in treating S. pseudintermedius canine infections.…”
Section: Current and Future Treatment Options For Staphymentioning
confidence: 99%
“…Endolysins act to hydrolyse the peptidoglycan layer of the bacterial host from within, resulting in the destruction of the cell wall and the release of phage progeny, to infect neighbouring target cells and continue the phage life cycle [ 132 ]. One study expressed and purified the lysin (Lys-phiSA012) from the previously mentioned phiSA012 phage, which had somewhat weak activity against S. pseudintermedius , whereas its endolysins, Lys-phiSA012, had clear lytic activity toward the S. pseudintermedius isolates [ 130 ]. Similarly, a secondary study also expressed and purified endolysins from another Staphylococcal phage ( Staphylococcus phage K); the endolysins showed lytic activity against the various Staphylococci strains obtained from canine pyoderma lesions [ 133 ].…”
Section: Current and Future Treatment Options For Staphymentioning
confidence: 99%
“… Nakamura et al (2020) investigated the action of both phage phiSA012 and its lysin Lys-phiSA012 against multidrug-resistant staphylococcal isolates of canine origin. While the ability of the phage to lyse the staphylococcal isolates was not significant, the lytic activity of the lysin was far more impressive.…”
Section: Phage Lysinsmentioning
confidence: 99%
“…To this end, many regulatory authorities across the globe have ensured stringent evaluation and validation of new manufacture serological assays for COVID-19. Although there are a lot of platforms for serological testing, including enzyme-linked immunosorbent assays (ELISAs), lateral-flow antibody assays (LFAs), bead-based assays based on Luminex technology, and automated serology platforms, most of the tests being evaluated across a number of African countries are based on LFAs [35,36]. This could be attributed to the fact that most countries in Sub-Saharan African have experience utilizing rapid diagnostic tests LFA devices for HIV and malaria, hence making LFAs the most preferred [37].…”
Section: Evaluation and Validation Of Rapid Diagnostic Testmentioning
confidence: 99%